Biosorption of mercury by Macrocystis pyrifera and Undaria pinnatifida: Influence of zinc, cadmium and nickel - Plaza Cazón, Josefina del Carmen (2011)
This study investigated the adsorption of Hg(II) on Macrocystis pyrifera and Undaria pinnatifida in monometallic system in the presence of Zn(II), Cd(II) and Ni(II). The two biosorbents reached the same maximum sorption capacity (qm = 0.8 mmol/g) for mercury. U. pinnatifida showed a greater affinity (given by the coefficient b of the Langmuir equation) for mercury compared to M. pyrifera (4.4 versus 2.7 L/mmol). Mercury uptake was significantly reduced (by more than 50%) in the presence of competitor heavy metals such as Zn(II), Cd(II) and Ni(II). Samples analysis using an environmental scanning electron microscopy equipped with an energy dispersive X-ray microanalysis showed that mercury was heterogeneously adsorbed on the surface of both biomaterials, while the other heavy metals were homogeneous distributed. The analysis of biosorbents by Fourier transform infrared spectrometry indicated that Hg(II) binding occurred on S=O (sulfonate) and N-H (amine) functional groups.